Menganalisis Pemodelan Persamaan Struktural Motivasi Berprestasi Mahasiswa terhadap Aspek-Aspek yang Berpengaruh dalam Pembelajaran Daring - Muh.Alwi; Risnashari Risnashari (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to measure and analyse the relationship between variables and obtain an accurate picture of the most significant factors in predicting student achievement motivation in online learning including internal, external, type of learning, psychological variables, fatigue variables, and achievement motivation of non Pendas Open University students in online learning. The research approach is ex-post facto quantitative method. With a sample size of 200 people, with research variables internal variables (X1), psychological variables (X2), fatigue variables (X3), external variables (X4), learning type variables (X5) and achievement motivation (Y). Data was collected using a questionnaire with a Likert scale of 1-4. Then the data was analysed using the Partial Least Square (PLS) method by looking at the p-value, by measuring the outer model and inner model. The results showed that external variables have a significant and high influence on achievement motivation with a statistical T value of 3.196, p-value 0.001, and F square 0.104. This indicates that external factors, such as environmental support and facilities, play an important role in motivating students. Internal variables and learning types also have a significant influence with a medium effect strength, indicated by an F square value of 0.061. Internal factors, including self-management and intrinsic motivation, as well as the type of learning methods used, play a moderate role in influencing students' motivation. Psychology also had a significant effect with moderate strength (F square 0.037), signalling the importance of students' mental and emotional state. Meanwhile, fatigue showed no significant effect on achievement motivation (T statistic 0.684, p-value 0.494).